La fréquence de l’alternance codique dans les groupes WhatsApp des étudiants libanais - Halawi, Ayman; Messarra, Nasri; Hardane, Jarjoura (Canadian Journal of Applied Linguistics, 2022)
The means of computer-mediated communication (CMC) and specifically the WhatsApp application, have led to innovative language practices in written communication. Among these practices is the high frequency of Code-Switching (CS), which is defined in this study as a switch from one written code to another within the same message. This quantitative study aims to automatically identify occurrences of Code-Switching in WhatsApp group chats. All through 14 months, we collected 168 219 messages from 30 WhatsApp groups. The study sample encompasses 1 482 bilingual students from 7 Lebanese universities. A computer tool "DACA" (automatic detection of Code-Switching and arabizi) has been developed to detect the frequency of this phenomenon resulting from languages contact. The results show that in the corpus, there are 15 342 occurrences of CS or 9,1% of the total number of messages. 70,5% of these CS occurrences are detected in messages in Arabizi, 17,9% in messages in English, 10,6% in messages in Arabic and 1% in messages in French. The results also reveal that CS in messages composed in Arabizi are quite often towards English (91,3% of the total number of these CS occurrences) and towards Arabizi in messages composed in English with the same percentage.